Marketing the work of smart management and its impact on the promotion of total quality management - Fadaws Odhaib, Amer (Opción, 2019)
The purpose of this study is to identify the impact of the marketing of smart management business in the promotion of total quality management, because of the current business environment in the development and contin- uous change in marketing areas, and to indicate their impact as an explana- tory variable to total quality management as a dependent variable. DESIGN AND METHODOLOGY The problem of the study was determined by sev- eral questions, the most important of which is whether the management of the Middle East Bank investment bank is an intellectual perception of the marketing of smart management and its dimensions and what is the bank’s ability to research in the promotion of total quality management. In order to achieve the objectives of the study, The sample of the study was select- ed in the Middle East Bank in Baghdad governorate. The study population was 133 individuals at all administrative levels. A random sample of (118) workers was targeted in the middle and upper administrations of the bank. R a number of assumptions concerning the main and sub-effect relationships between the variables of the study, and use the program ((Excel 2007, Spss for the purpose of data processing. Conclusions The study reached a set of theoretical and applied conclusions, most notably the impact of smart busi- ness management on the promotion of Total Quality Management (MQM) of the Middle East Bank. The study concluded with a set of recommenda- tions in the light of the conclusions reached.